Validation of a Short Questionnaire in English and French for Use in Patients with Persistent Upper Gastrointestinal Symptoms Despite Proton Pump Inhibitor Therapy: The Pass (Proton Pump Inhibitor Acid Suppression Symptom) Test. (1st June 2005) - Armstrong, David; van Zanten, Sander JO Veldhuyzen; Chung, Sharon A; Shapiro, Colin M; Dhillon, Sukhjeet; Escobedo, Sergio; Chakraborty, Bijan K; Mann, Vijay; Tanser, Lisa; Nevin, Krista
Abstract : BACKGROUND: The management of persistent symptoms during acid suppression therapy in patients with gastroesophageal reflux disease or dyspepsia might be improved if patient-physician communication regarding the presence and character of these persistent symptoms were facilitated. AIM: To validate a short, simple questionnaire (the Proton pump inhibitor [PPI] Acid Suppression Symptom [PASS] test), in English and French, to identify patients with persistent acid-related symptoms during PPI therapy and document their response to a change in therapy. METHODS: Patients with persistent acid-related symptoms on PPI therapy were interviewed to produce a draft, five-item questionnaire; content validity was evaluated by focus groups comprising English- and French-speaking patients. Psychometric validity was subsequently evaluated in a multicentre, family practice-based study of English- and French-speaking patients with persistent acid-related upper gastrointestinal symptoms despite PPI therapy. The PASS test, Global Overall Symptom scale, Gastrointestinal Symptom Rating Scale (GSRS), Quality of Life in Reflux and Dyspepsia questionnaire and Reflux Disease Questionnaire were completed at baseline and repeated after one week while patients continued their original PPI therapy. All patients then received esomeprazole 40 mg once daily for four weeks, after which all questionnaires and an evaluation of overall treatment effect were completed. RESULTS: Content validity was established in 20 English- and 16 French-speaking patients. Psychometric validation in 158 English- and 113 French-speaking patients revealed good-to-excellent test-retest reliability coefficients: 0.76 for English; 0.68 for French. For construct validity, the PASS test showed moderate-to-high correlation with the GSRS scale (0.51 for English; 0.43 for French). After four weeks of therapy, the PASS test score fell to zero in 30% of English- and 33% of French-speaking patients, while the Global Overall Symptom score fell to one (no symptoms) in 32% of patients (English- and French-speaking); the PASS test demonstrated good responsiveness in comparison with the GSRS, Reflux Disease Questionnaire and Quality of Life in Reflux and Dyspepsia questionnaire. CONCLUSION: The five-item PASS test is a valid tool for the evaluation of persistent acid-related symptoms in patients receiving PPI therapy. It demonstrates good content validity, test-retest reliability, responsiveness and construct validity in both English and French forms. The PASS test is a simple, clinically applicable tool for the identification of patients with persistent acid-related symptoms during therapy and the assessment of their responses to a change in therapy.